Vegetasi Gulma pada Tanaman Ubi Kayu (Manihot esculenta) Di Kabupaten Oku Timur Sumatera Selatan - Syamsul Rizal; Siti Nuryatin; Trimin Kartika; Marmaini Marmaini (Universitas PGRI Palembang, 2022)
Research on Weed Vegetation in Â Cassava (Manihot esculenta) was carried out from March to April 2019 at a cassava plantation in East OKU Regency, South Sumatra. This study aims to determine the composition and structure of weeds in cassava plantations. This study used a quadratic method with 7 plots of 2 x 2 m in size. The parameters observed were density (K), relative density (KR), frequency (F), relative frequency (FR), Importance Value Index (INP) and Community Diversity Index (H '). The results showed 11 types of weeds, namely Ageratum conyzoides, Erechtites valerianifolia, Chromolaena odorata, Asystasia gangetica, Mimosa pudica, Boreria alata, Calapogonium caereuleum, Cleome rutidosperma, Physalis angulata, Cyperus rotundus, and Axonopus compressus. The dominant species was Ageratum conyzoides INP 47.43%. Species diversity is moderate with H 'value.